Ion temperature clamping in Wendelstein 7-X electron cyclotron heated plasmas. (25th October 2021) - Beurskens, M.N.A.; Bozhenkov, S.A.; Ford, O.; Xanthopoulos, P.; Zocco, A.; Turkin, Y.; Alonso, A.; Beidler, C.; Calvo, I.; Carralero, D.; Estrada, T.; Fuchert, G.; et al.
Abstract: The neoclassical transport optimization of the Wendelstein 7-X stellarator has not resulted in the predicted high energy confinement of gas fueled electron-cyclotron-resonance-heated (ECRH) plasmas as modelled in (Turkin et al 2011 Phys. Plasmas 18 022505) due to high levels of turbulent heat transport observed in the experiments. The electron -turbulent-heat transport appears non-stiff and is of the electron temperature gradient (ETG)/ion temperature gradient (ITG) type (Weir et al 2021 Nucl. Fusion 61 056001). As a result, the electron temperature T e can be varied freely from 1 keV–10 keV within the range of P ECRH = 1–7 MW, with electron density n e values from 0.1–1.5 × 10 20  m −3 . By contrast, in combination with the broad electron-to-ion energy-exchange heating profile in ECRH plasmas, ion -turbulent-heat transport leads to clamping of the central ion temperature at T i ∼ 1.5 keV ± 0.2 keV. In a dedicated ECRH power scan at a constant density of 〈 n e 〉 = 7 × 10 19  m −3, an apparent 'negative ion temperature profile stiffness' was found in the central plasma for ( r / a < 0.5), in which the normalized gradient ∇ T i / T i decreases with increasing ion heat flux. The experiment was conducted in helium, which has a higher radiative density limit compared to hydrogen, allowing a broader power scan. This 'negative stiffness' is due to a strong exacerbation of turbulent transport with an increasing ratio of T e / T i in this electron-heated plasma. This finding is consistent with electrostatic microinstabilities, such as ITG-driven turbulence. Theoretical calculations made by both linear and nonlinear gyro-kinetic simulations performed by the GENE code in the W7-X three-dimensional geometry show a strong enhancement of turbulence with an increasing ratio of T e / T i . The exacerbation of turbulence with increasing T e / T i is also found in tokamaks and inherently enhances ion heat transport in electron-heated plasmas. This finding strongly affects the prospects of future high-performance gas-fueled ECRH scenarios in W7-X and imposes a requirement for turbulence-suppression techniques.